O37. Radiobiological evaluation of prostate 3D-CRT using the Pinnacle3 TPS. (September 2016) - Fourie, H.; Burger, H.
Abstract : Introduction: Superior tumour control of high risk prostate cancer requires doses in excess of 70 Gy, but is limited by the normal tissue constraints. Additionally, increasing evidence suggests prostate cancer has an α / β value closer to that of late responding tissues or even lower. Conventionally, physiological dose distributions and DVH statistics are used for plan evaluation. This study investigates plan evaluations through radiobiological modelling of Tumour Control Probability (TCP) and Normal Tissue Complication Probability (NTCP) and their sensitivity to fractionation schedules. Materials and methods: A departmental investigation was done using 10 random 3D conformal external photon beam prostate radiotherapy plans. The effects of dose escalation, dose per fraction, and tumour radiosensitivity to fractionation ( α / β ) on prostate TCP and rectal NTCP were investigated using the commercial Pinnacle 3 (v. 9.8) treatment planning system's Biological Plan Evaluation module. Results: As expected, an increase in TCP and NTCP was observed when increasing the total prescribed dose; additionally, the rectal NTCP was found to be correlated to the volume of rectum irradiated. TCPs remained relatively constant w.r.t. α / β values for conventional dose/fraction regimes, but increased with higher doses/fraction, especially at lower α / β values. For example, for two typical fractionation regimes (2 Gy x 37 fractions (SFRT) vs. 2.5 Gy × 28 fractions (HFRT)) the Pinnacle model was used to predict NTCP ( α / β  = 3) and TCP for α / β  = 10 & 3 respectively. The TCP was relatively insensitive to the α / β changes for the SFRT regime (93.1% & 92.8%), whereas the HFRT regime showed a larger percentage change (91.2% & 96.0%). The NTCPs were 6.4% and 8.5% for the respective fractionation schedules regardless of tumour α / β . Conclusion: If the α / β value for prostate cancer is lower than that of late responding normal tissues, radiobiological evaluations suggest that the tumour would be more sensitive to changes in the dose/fraction and a higher TCP could be obtained without a significant increase in rectal NTCP; this is exploited through hypofractionation.